A study on the molecular existing interactions in nanoherbicides: A chitooligosaccharide/tripolyphosphate loaded with paraquat case - Moreno, Adrian; Jordana, Axel; Grillo, Renato [UNESP]; Fraceto, Leonardo F. [UNESP]; Jaime, Carlos (Elsevier B.V., 2019)
Several modified release nanoformulations have been developed for pesticides to improve their physicochemical stability as well as to reduce their toxicity and bioavailability in the environment and human health. Nevertheless, studies related to the molecular interactions of pesticides with nanocarriers are scarce, although the study of the molecular interactions of nanoparticles with pesticides is important to correlate with the nanoparticle structure and biological activity. Thus, the goal of this study is to gain insights on the molecular interactions between a model of nanoparticles (chitosan/tripolyphosphate, CH/TPP) and the herbicide paraquat (PQ). The system was defined using a very simple Coarse-Grained model where sets of atoms having similar properties are replaced by beads (or pearls). Several dissipative particle dynamics (DPD) simulations with different PQ concentrations were initially performed to find the conditions for breaking the triple interaction. All simulations yielded strong CH/TPP/PQ interactions, and the introduction of a new type of bead for distinguishing between the CH nitrogen atoms and the PQ nitrogen atoms appeared to be necessary. Design of experiments was used for finding reasonable CH/TPP/PQ interaction values. Only one simulation among all the carried out had quite good interaction and large areas showing the CH/TPP/PQ triple interaction. Those repulsion constant values were used along this research. The effect of the order of addition was also studied. The results from our simulations and experimental issues allow ensuring that different ways of adding CH, TPP, and PQ definitely affect the ending results.
Keywords: Chitosan; Paraquat; Nanopesticides; Molecular interactions; Dissipative particle dynamics